Prevalence of Eating Disorders in Adults with Celiac Disease - V. Passananti; M. Siniscalchi; F. Zingone; C. Bucci; R. Tortora; P. Iovino; C. Ciacci (Gastroenterology Research and Practice)
Background. Symptoms of celiac disease negatively impact social activities and emotional state. Aim was to investigate the prevalence of altered eating behaviour in celiac patients. Methods. Celiac patients and controls completed a dietary interview and the Binge Eating Staircases, Eating Disorder Inventory (EDI-2), Eating Attitudes Test, Zung Self-Rating Depression Scale, State Trait Anxiety Inventory Forma Y (STAI-Y1 and STAI-Y2), and Symptom Check List (SCL-90). Results. One hundred celiac adults and 100 controls were not statistically different for gender, age, and physical activity. STAI-Y1 and STAI-Y2, Somatization, Interpersonal, Sensitivity, and Anxiety scores of the SLC-90 were higher in CD patients than controls. EDI-2 was different in pulse thinness, social insecurity, perfectionism, inadequacy, ascetisms, and interpersonal diffidence between CD and HC women, whilst only in interceptive awareness between CD and HC men. A higher EAT-26 score was associated with the CD group dependently with gastrointestinal symptoms. The EAT26 demonstrated association between indices of diet-related disorders in both CD and the feminine gender after controlling for anxiety and depression. Conclusion. CD itself and not gastrointestinal related symptoms or psychological factors may contribute pathological eating behavior in celiac adults. Eating disorders appear to be more frequent in young celiac women than in CD men and in HC.